Motivating the study of international trade: A classroom activity. Issue 4 (1st October 2016) - Jensen, Sherry
ABSTRACT: In this article, the author describes a classroom activity for use in introductory economics courses to motivate the study of international trade. The learning activity highlights the importance of international trade in students' everyday lives by having students inventory their on-hand belongings and identify where the items were manufactured. Students find that even among the relatively few possessions they have with them in the classroom, dozens of countries are represented. Further, the activity can be used to prompt discussions on the benefits of trade, trade patterns, comparative advantage, specialization, and trade regulations, as well as welfare effects of those regulations.